Learning Design for Future Higher Education – Insights From the Time of COVID-19 - Dumulescu, Daniela; Pop-Păcurar, Irina; Necula, Constantin Valer (Frontiers in Psychology, 2021)
The COVID-19 pandemic brought many challenges in higher education. All teaching and learning activities were moved online. Universities had to provide adapted solutions to facilitate learning and maintain students’ engagement. Online education implies creating new learning environments with the help of digital technologies. Beyond the process of acquisition of iknowledge, teachers needed to facilitate cooperative learning, to build positive relations, andreduce negative emotions.. We provide some expert insights based on empirical observations on teaching and assessment practices connected with psychology models applied in education. The aim of the paper is to formulate specific learning design recommendations for developing effective didactic strategies and addressing the current worldwide critical issue: dealing with digitization of higher education in the immediate future. We propose a model of university classes aimed at bringing together our experience as teachers of psychology and didactics with evidence-based cognitive-educational theories and practices. The result is an example of instructional work-model based on the complex dynamic between cognitive, emotional-motivational and social aspects of learning in online settings. The effectiveness of university teaching in the post-digital era is strongly connected with the ability to create cognitive-transferable learning experiences, emotionally safe learning environments, while promoting an active autonomy-focused approach for self-regulated learning.